2010
DOI: 10.1016/j.bandl.2009.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Speech errors in progressive non-fluent aphasia

Abstract: The nature and frequency of speech production errors in neurodegenerative disease have not previously been precisely quantified. In the present study, 16 patients with a progressive form of nonfluent aphasia (PNFA) were asked to tell a story from a wordless children's picture book. Errors in production were classified as either phonemic, involving language-based deformations that nevertheless result in possible sequences of English speech segments; or phonetic, involving a motor planning deficit and resulting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(81 citation statements)
references
References 44 publications
2
76
0
3
Order By: Relevance
“…While some observations have associated speech-sound errors with a disorder of motor-speech planning known as AOS, 3,7 our quantitative analyses suggest that these errors are much more often due to a linguistic disruption of the phonologic processing system. 27 Regardless of the basis for speech-sound errors in PNFA, a regression analysis in the present study revealed that reduced speech fluency is not related to speech-sound errors.…”
Section: Resultsmentioning
confidence: 90%
“…While some observations have associated speech-sound errors with a disorder of motor-speech planning known as AOS, 3,7 our quantitative analyses suggest that these errors are much more often due to a linguistic disruption of the phonologic processing system. 27 Regardless of the basis for speech-sound errors in PNFA, a regression analysis in the present study revealed that reduced speech fluency is not related to speech-sound errors.…”
Section: Resultsmentioning
confidence: 90%
“…13,15,36 Apraxia of speech (AOS) has also been described in CBD on its own and coexisting with aphasia, 20,32 though challenges in diagnosing AOS limit efforts to estimate its frequency. Some consider AOS a speech disorder rather than language dysfunction 37 ; consensus has been elusive. Speech abnormalities in general were described in 53% of cases (23% at presentation) (table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with our findings, Shattuck-Hufnagel and Klatt (1979) reported no tendency to simplify in the speech errors of adult controls with fluent speech. Also Ash et al (2010) found no markedness effects in patients with progressive aphasia that they described as non-fluent, but who showed no evidence of articulatory difficulties (e.g., few phonetic errors, high rates of vowel errors).…”
Section: Implications For Linguistic Theoriesmentioning
confidence: 94%
“…Slurred phonemes: A stretch of speech or a whole word produced in a slurred fashion; systematically slurred speech is associated with dysarthria (e.g., Duffy et al, 2007), but stretches of slurred speech also occur in patients with AoS; 2. Distorted phonemes: Included in this category are lenitionswell-formed phonemes produced with less articulatory force (e.g., see Ash et al, 2010) -and phonemes produced with a perceptible deviation from the target in place, manner or timing (see Kent and Rosenbek, 1983;Odell et al, 1990;McNeil et al, 1990); 3. An audible or, more rarely, visual effort in producing the word, generally at word beginning (for initiation difficulties see Kent and Rosenbek, 1983;Strand and McNeil, 1996; for effortful trial and error and groping, see McNeil et al, 1990McNeil et al, , 2009Odell et al, 1990).…”
Section: Phonetic Errors and Experimental Classificationmentioning
confidence: 99%